(untitled) (Research, Society and Development, 2024)
The skin is the largest human organ; injuries to this structure can result in functional limitations, involving a complex tissue repair process. Chronic wounds represent a major public health problem in Brazil, with an impact on costs and quality of life of patients. Phytotherapy, especially with the use of Anacardium occidentale, known as cashew tree, has been identified as an efficient therapy to promote wound healing, although there is controversy about its efficacy. This work aims to conduct a narrative review on the therapeutic potential, efficacy and safety of Anacardium occidentale Linn in the treatment of skin lesions, based on the literature available in the main databases. Among the articles analyzed, 8 were selected and organized in a table in chronological order by year of publication, as well as objectives, methodologies of the evaluated article, results and conclusions of each study selected for the preparation of the results and discussions. The use of A. occidentale has shown benefits in the treatment of several diseases, such as skin lesions, inflammations, oral diseases and gastrointestinal processes. Therapeutic effects include anti-inflammatory and healing action, in addition to stimulating tissue repair, with different parts of the plant being used. The study highlighted that the cashew tree has therapeutic properties, mainly in the treatment of inflammatory skin lesions due to its active metabolites. Despite being an accessible and low-cost medicinal plant, more toxicological research is needed to confirm the safety of its use. A. occidentale shows promise for therapeutic use, but more studies are needed to define efficacy and safety.